EFL NEW UNIVERSITY STUDENTS’ STRATEGIES TO COPE WITH WRITING FOR ACADEMIC PURPOSES IN ONLINE LEARNING - Chelsea Indy Karisma; Sri Lestari (IKIP Siliwangi, 2023)
The study aimed to explore EFL new university students’ challenges and strategies to cope with academic writing in the online learning process. This study focuses on how EFL students in higher education adapt and adjust to the academic situation by exploring their challenges and strategies to write for academic purposes, especially in the online learning process. The study involves freshmen in the English Language Education department of a private university in Jakarta, Indonesia, who are taking English writing skills courses. This study was conducted using a qualitative approach, to know the challenges and strategies used by university students. This study used purposeful sampling, by choosing the participant that matches the requirements. The data collection of this study used a questionnaire with an open-ended question, and semi-structured interview to investigate the students' experience of writing for academic purposes in online learning. This study revealed that EFL new university students have various difficulties and faced some challenges in learning writing for academic purposes in online learning. However, it is found that EFL new university students have their own strategies of writing for academic purposes in online learning. Keywords: Academic Writing; EFL New University Student; Writing for Academic Purposes